(untitled) (Applied Biological Research, 2025)
Medicinal plants serve as a valuable source of bioactive compounds essential for disease prevention and therapeutic interventions. This study investigated the phytochemical composition and evaluated the antioxidant, antimicrobial, and antifungal potential of Fimbristylis ferruginea (L.) Vahl. Phytochemical screening of ethyl acetate, ethanol, acetone, and chloroform extracts revealed the presence of phenolics, flavonoids, terpenoids, alkaloids, glycosides, and anthraquinones. Among the extracts, ethyl acetate exhibited the highest phenolic content (1.62 mg GAE g⁻¹), while chloroform extract showed the highest flavonoid content (59 mg QE g⁻¹). Antioxidant activity was assessed using DPPH and FRAP assays, whereas antimicrobial and antifungal activities were evaluated against Staphylococcus aureus, Escherichia coli, Shigella flexneri, Enterococcus faecalis, Candida albicans, and Fusarium oxysporium through agar well diffusion and MIC/MBC methods. The ethyl acetate and chloroform extracts demonstrated significant bioactivity. Advanced analytical techniques including gas chromatography–mass spectrometry (GC-MS), ultraviolet–visible (UV-Vis) spectroscopy, Fourier transform infrared (FT-IR) spectroscopy, and nuclear magnetic resonance (NMR) spectroscopy were employed for the identification and structural elucidation of active compounds. A key compound identified was 1,2-benzenedicarboxylic acid, bis(2-ethylhexyl) ester. The findings indicate the promising pharmaceutical and nutraceutical potential of F. ferruginea.